Do Leadership, Career Progression, Compensation, and Burn-out Moderated by Work Motivation Affect Employee Performance in Digital Companies? - Suprapto, Hugo Aries; Setyastanto, Albertus Maria; Widiyarto, Sigit; Poon, Yuan-Sheng Ryan (PT. Riset Press International, 2026)
This study examines how leadership, compensation, career progression, and burn-out—conditional on work motivation—affect employee performance in digital companies. Effective leadership, fair compensation, transparent career progression, and proactive burnout management—conditioned by employees’ intrinsic and extrinsic work motivation—collectively drive engagement, productivity, creativity, teamwork, well-being, retention, efficiency, and organizational performance in digital companies long term growth. A quantitative approach was used with questionnaires and company documentation collected from 213 employees across four digital firms in Jakarta between January and April 2024. Data were analyzed using SEM-PLS. the result was leadership positively and significantly improves employee performance. Compensation is negatively associated with, indicating higher pay alone did not translate into better performance. Career progression positively and significantly enhances performance. Burn-out showed a positive association with reported performance, suggesting possible short-term productivity despite wellbeing costs. Work motivation has a positive direct effect on performance. As a moderator, work motivation weakens the effects of leadership and compensation on performance, while it strengthens the effects of career progression and digital learning . All reported effects are statistically significant.